The desert and the sea : 977 days captive on the Somali pirate coast - Moore, Michael Scott (New York, N.Y. : Harper Wave, 2018)
Chronicles the author's three years of captivity by Somali pirates, offering an exploration of foreign policy, religious extremism, and the costs of survival in the process.
Keywords: Moore, Michael Scott; Moore, Michael Scott; Kidnapping victims -- Somalia; Kidnapping -- Somalia; Hostages -- Somalia; Pirates -- Somalia; Kidnapping -- Somalia; Hostages -- Somalia; Pirates -- Somalia